RATIONALE OF ANTIBIOTIC PRESCRIPTION IN PATIENTS VISITING A TERTIARY CARE SOUTH INDIAN HOSPITAL - AHMED, MOHAMED; KUMAR, PAWAN; D.V. KISHORE; KUMAR, PRABHAT; KAUSER, RUBEENA; ALI, MOAZAM (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Antimicrobials are the class of drugs that are used irrationally in most cases leading to rise in instances of antimicrobial resistance altering the effect of such agents. Antimicrobial resistance has become a critical issue universally nerving the need to monitor the utilization pattern and rationality in prescribing of antibiotics. This helps in selection of most appropriate antibiotic for the specific patient and achieving the goals of the therapy. Methods: A prospective cross-sectional study with a sample size of 600 participants was conducted in department of general medicine of a tertiary care hospital. Inpatients prescribed with antibiotics were included in the study and their case sheets were reviewed to analyzing the prescribing pattern. The medication usage pattern was then assessed for rationality in prescribing was evaluated. The results obtained were statistically analyzed using SPSS Software. Results: It is noted that a more number of males participated and the greatest number of the patients were from the age group of 31-45. The diagnosis found in the majority of the patients was respiratory tract infection followed by others. On scrutinizing the prescriptions, it was noted that cephalosporins and penicillins were most often prescribed, and on an average single, antibiotic was frequently used with the preferred route of administration in most of the prescriptions being injection route. Though many of the antibiotics were prescribed empirically, it was observed that 59% of them were most appropriately dosed and maximum patients that are around 57% were cured from their illnesses. Conclusion: This study provided important baseline information on antimicrobial use within a large tertiary care teaching hospital and identified potential targets for future antimicrobial stewardship programs. The culture and sensitivity testing suggested that the drug resistance was more for most commonly prescribed antibiotics in the hospital. Increased targeted prescribing based on sensitivity tests will bring down the high use of empiric broad-spectrum antibiotic use.